Ending Poverty: Strengthening Urban Container Gardening - Mamoko, Joyce Roldan Z.; Agohob, Sheryl Ann R.; Saturinas, Adrian T. (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
The COVID-19 pandemic augmented with the threats brought by climate change resulted in a ballooning number of poor across the globe. Hence, making it challenging to achieve the 2030 Agenda for Sustainable Development Goals established by the United Nations. This paper aims to identify long-term solutions to address the posing threats brought by the crisis that will lead to the eradication of poverty. Urban Container Gardening is one of the most efficient and attainable ways of solving hunger and reducing waste. It will also be a good source of income since agricultural harvests are largely consumed daily as people are becoming more health conscious. However, this paper concludes that the current urban container gardening system is not sustainable due to the lack of support from the government. This paper also examines the role of the government in facilitating a free market for all, where people are allowed to offer and sell their harvests. Finally, this study presumes the importance of mandatory savings and insurance for the vendors to transform their lives from poverty to financial security.